Binge alcohol drinking alters the differential control of cholinergic interneurons over nucleus accumbens D1 and D2 medium spiny neurons - Kolpakova, Jenya; van der Vinne, Vincent; Gimenez-Gomez, Pablo; Le, Timmy; Martin, Gilles E. (Frontiers in Cellular Neuroscience, 2022)
Animals studies support the notion that striatal cholinergic interneurons (ChIs) play a central role in basal ganglia function by regulating associative learning, reward processing, and motor control. In the nucleus accumbens (NAc), a brain region that mediates rewarding properties of substance abuse, acetylcholine regulates glutamatergic, dopaminergic, and GABAergic neurotransmission in naïve mice. However, it is unclear how ChIs orchestrate the control of these neurotransmitters/modulators to determine the synaptic excitability of medium spiny neurons (MSNs), the only projecting neurons that translate accumbens electrical activity into behavior. Also unknown is the impact of binge alcohol drinking on the regulation of dopamine D1- and D2 receptor-expressing MSNs (D1- and D2-MSNs, respectively) by ChIs. To investigate this question, we optogenetically stimulated ChIs while recording evoked and spontaneous excitatory postsynaptic currents (sEPSCs) in nucleus accumbens core D1- and D2-MSN of ChAT.ChR2.eYFPxDrd1.tdtomato mice. In alcohol-naïve mice, we found that stimulating NAc ChIs decreased sEPSCs frequency in both D1- and D2-MSNs, presumably through a presynaptic mechanism. Interestingly, ChI stimulation decreased MSN synaptic excitability through different mechanisms in D1- vs D2-MSNs. While decrease of ChI-mediated sEPSCs frequency in D1-MSNs was mediated by dopamine, the same effect in D2-MSNs resulted from a direct control of glutamate release by ChIs. Interestingly, after 2 weeks of binge alcohol drinking, optogenetic stimulation of ChIs enhanced glutamate release in D1-MSNs, while its effect on D2-MSNs remained unchanged. Taken together, these data suggest that cholinergic interneurons could be a key target for regulation of NAc circuitry and for alcohol consumption.